2010
DOI: 10.1159/000288521
|View full text |Cite
|
Sign up to set email alerts
|

Acute Complications of Crohn’s Disease: Comparison of Multidetector-Row Computed Tomographic Enterography with Magnetic Resonance Enterography

Abstract: Objective: To compare multidetector-row computed tomographic (MDCT) enterography with magnetic resonance (MR) enterography performed upon acute exacerbation of Crohn’s disease. Subjects and Methods: Fifty-seven patients (mean age 33.5) with proven Crohn’s disease and symptoms suggesting acute exacerbation were prospectively included. After oral administration of 1–2 liters of 5% methylcellulose, MDCT and MR enterography were performed on each patient (mean delay <24 h). Three radiologists blindly and independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…We found that MR was also accurate at identifying ileo‐enteric and ileosigmoid fistulae (Fig. a,b) in common with previous studies . We could not, however, accurately identify the number of fistulae when more than one was present, either on MR or at surgery.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found that MR was also accurate at identifying ileo‐enteric and ileosigmoid fistulae (Fig. a,b) in common with previous studies . We could not, however, accurately identify the number of fistulae when more than one was present, either on MR or at surgery.…”
Section: Discussionsupporting
confidence: 68%
“…Concerns about ionizing radiation involved in these investigations [1,2] and improvements in magnetic resonance (MR) technology have prompted the increased use of MR imaging of the small bowel as a radiation-free alternative. In order to view small bowel pathology, adequate bowel distension is needed and this is achieved by drinking contrast (MR enterography [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]) or by contrast introduction via a nasoduodenal tube inserted under fluoroscopic control (MR enteroclysis [21][22][23][24][25][26][27][28][29][30]). MR enteroclysis may achieve better jejunal distension and mucosal visualization than MR enterography [7] but no statistical difference has been found between these techniques in a direct comparison [15].…”
Section: Introductionmentioning
confidence: 99%
“…The literature search revealed 2501 abstracts related to MRI use in CD. Of these, 244 were retrieved and 62 studies were deemed appropriate for inclusion (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In young adults MR enterography showed a diagnostic value similar to MDCT enterography at least for acute complications of CD, such as fistulas and abscesses [79] . The abscesses can be treated by percutaneous interventions.…”
Section: Penetrating Diseasementioning
confidence: 75%